2016
DOI: 10.11646/phytotaxa.270.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Bellevalia behcetii sp. nov. (Asparagaceae): a new species from South Eastern Anatolia, Turkey

Abstract: Bellevalia behcetii (Asparagaceae) is described and illustrated as a new species from Şırnak province in South Eastern Anatolia (Turkey). It is morphologically similar to B. paradoxa but easily differs in several morphological characters. Diagnostic morphological characters, a full description and detailed illustrations of the new species are provided. A quantitative morphometric analysis was carried out to check the diagnostic characters of Bellevalia behcetii with respect to morphologically related species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Bas ¸er et al ( 2019) did not characterize the pollen types, but mentioned the prolate pollen form in relation to the Bellavalia species (B. hakkariensis, B. siirtensis and B. kurdica). In the SEM analyzes concerning with Bellevalia behcetii made by Pınar et al (2016), was indicated that the species also has suprolate-shaped pollen. Thus, according to the SEM micrographs given in the related articles, the taxa have E-type pollen as in B.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bas ¸er et al ( 2019) did not characterize the pollen types, but mentioned the prolate pollen form in relation to the Bellavalia species (B. hakkariensis, B. siirtensis and B. kurdica). In the SEM analyzes concerning with Bellevalia behcetii made by Pınar et al (2016), was indicated that the species also has suprolate-shaped pollen. Thus, according to the SEM micrographs given in the related articles, the taxa have E-type pollen as in B.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…kurdica ). In the SEM analyzes concerning with Bellevalia behcetii made by Pınar et al (2016), was indicated that the species also has suprolate‐shaped pollen. Thus, according to the SEM micrographs given in the related articles, the taxa have E‐type pollen as in B .…”
Section: Discussionmentioning
confidence: 99%
“…collected previously. Specimens deposited in the Van Yüzüncü Yıl University Herbarium (VANF) and from relevant literature were used in the comparisons (Losinskaja 1935;Feinbrun 1940;Wendelbo 1984Wendelbo , 1985Wendelbo , 1990Özhatay et al 1991;Cowley et al 1994; Ö z h a t a y 2 0 0 0 ; Persson 2 0 0 6 ; Tu g a y 2 0 1 2 ; Uzunhisarcıklı et al 2013;Gürdal et al 2014;Karabacak et al 2014Karabacak et al , 2015Yıldırım et al 2014;Pınar et al 2016). The unidentified plants were observed and collected from the same plot in 2016 and 2017.…”
Section: Methodsmentioning
confidence: 99%
“…Further studies performed by local botanists has resulted in the addition of 8 new species to the Flora of Turkey: B. malatyaensis Uzunhisarcıklı & Duman (Uzunhisarcıklı et al 2013) (Şahin et al 2016), andB. behcetii Pınar, Eroğlu &Fidan (Pınar et al 2016). Today, 30 Bellevalia species are reported in Turkey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation